Pentingnya Partisipasi Umat dalam Pengembangan Komunitas Basis Gerejawi di Paroki St. Maria Bunda Para Bangsa Gunungsitoli - Mawarni Gea; Bartolomeus Sihite; Renata Rufiana Gowasa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
The purpose of this writing is to explain the importance of community participation in KBG development in St. Mary, Mother of the Gunungsitoli Nation. Where the presence of the KBG requires the people within it to become more actively involved in every KBG activity. The problem in this research is how the community participates in the development of KBG in St. Mary's Parish. Mary, Mother of the Gunungsitoli Nation. The aim is to encourage congregational participation in the development of KBG in St. Mary, Mother of the Gunungsitoli Nation. This research approach is descriptive qualitative. Data collection techniques through interview observation and documentation. The research carried out revealed that KBG is an association of believers consisting of 10-15 families to pray together, share their faith, and listen to the Word of God. In KBG, people are generally less active in KBG activities, sometimes there are also people who are less aware of their duties and responsibilities in KBG. This research shows that through Ecclesiastical Base Community meetings, people can grow their faith in Christ.